2020
DOI: 10.3390/cancers12061414
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines and ctDNA Are Biomarkers for Progression in Advanced-Stage Melanoma Patients Receiving Checkpoint Inhibitors

Abstract: Purpose: Checkpoint inhibitors have significantly improved treatment of metastatic melanoma. However, 40–60% of patients do not respond to therapy, emphasizing the need for better predictive biomarkers for treatment response to immune checkpoint inhibitors. Prorammed death-ligand 1(PD-L1) expression in tumor cells is currently used as a predictive biomarker; however, it lacks specificity. Therefore, it is of utmost importance to identify other novel biomarkers that can predict treatment outcome. Experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
1
12
1
Order By: Relevance
“…Analysis of ctDNA has proven to be useful not only for examining the genomic status of tumors but also for shedding light on other aspects of the disease, including the immune status. Pedersen et al [ 39 ] reported that the baseline ctDNA level was closely related to the therapeutic effect of immune checkpoint inhibitors in patients with metastatic melanoma. DNA can stimulate the immune response via regulation of IFN and other proinflammatory mediators in immune cells in a manner dependent on structure and sequence (REFS), and immune cell activation can be observed with DNA alone or in complex with other molecules [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of ctDNA has proven to be useful not only for examining the genomic status of tumors but also for shedding light on other aspects of the disease, including the immune status. Pedersen et al [ 39 ] reported that the baseline ctDNA level was closely related to the therapeutic effect of immune checkpoint inhibitors in patients with metastatic melanoma. DNA can stimulate the immune response via regulation of IFN and other proinflammatory mediators in immune cells in a manner dependent on structure and sequence (REFS), and immune cell activation can be observed with DNA alone or in complex with other molecules [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, more studies correlating metagenomic and metatranscriptomic data of GM to outcomes of melanoma patients on immunotherapy ought to be performed as the functional capacity may be more important rather than individual GM family/order/species. In addition, we eagerly await the outcome of multiple large-scale RCTs involving FMT in the context of ICB-refractory melanoma such as NCT04577729 and NCT04988841 (PICASSO) (ClinicalTrails.gov).We foresee that together with other promising biomarkers, GM composition and diversity will be integrated into a multiparameter model to accurately predict which subset of melanoma patients are likely to respond to ICB[ 10 , 11 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in ctDNA have been reported to provide earlier markers of response to therapy than morphological changes in tumor size [33,34], and if individual mutations are unique to an individual metastasis, it may be possible to track the progress of individual metastases over time, analogous to the lesion-specific information provided by noninvasively imaging of a metastasis during treatment [4,35]. A recent study in metastatic melanoma reported that ctDNA levels at baseline and early follow-up can predict disease progression in patients treated with checkpoint inhibitors [36]. A further study showed that baseline ctDNA detection was associated with poor prognosis in metastatic BRAF or NRAS-mutated melanoma patients [37].…”
Section: Discussionmentioning
confidence: 99%